THE EFFECT OF CAREER DEVELOPMENT ON PERFORMANCE THROUGH EMPLOYEE ENGAGEMENT AS AN INTERVENING VARIABLE - Malik , M. Musthabiq Dzikril; Herlambang, Toni; Thamrin, Mohammad; Satoto, Eko Budi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This research is intended to analyze the influence of career development on employee engagement and employee performance, analyze the influence of employee engagement on employee performance, and analyze the role of employee engagement in mediating career development on employee performance. Method: This research uses explanatory research. The population in this study were all sub-district employees in Jember Regency who in taking samples applied the Saturated Sample method/Census Method, the data analysis technique used in this research was path analysis using the SEM (Structural Equation Modeling) model or Structural Equation Model with the Warp PLS 7.0 program. Results: The research results show that career development influences employee engagement. Career development influences employee performance. Employee engagement influences employee performance. And, career development influences employee performance through employee engagement. Novelty: This research uses a model of the effect of career development on employee performance by involving employee engagement as intervening. Thus, this model is the answer to the existing research gap related to employee performance.